Effect of abrasive vibration on microstructure evolution and material removal of SiC CMP - Ailing TANG; Zewei YUAN; Meiling TANG; Ying WANG (Jin'gangshi yu moliao moju gongcheng, 2024)
To address issues related to abrasion, agglomeration, and the challenges of mechanical and chemical release during chemical mechanical polishing (CMP), a vibration-assisted CMP method is employed. Molecular dynamics simulation analyze the dynamic evolution of frequency, amplitude, and indentation depth, along with the dicing speed of abrasive vibration on the workpiece's surface. It reveals the mechanism behind enhanced material removal and improved surface quality facilitated by vibration. The effectiveness and removal mechanism of vibration-assisted CMP are validated through process testing and surface composition analysis. The results show that atomic potential energy and temperature on the workpiece surface can be effectively improved by appropriately increasing vibration frequency, vibration amplitude, indentation depth, and abrasive particle cutting speed. Abrasive vibration contributes to increased atomic disorder on the workpiece surface, facilitating the participation of silicon carbide in oxidation reactions. This process results in the formation of an oxide layer, which is mechanically removed. Polishing tests and composition analyses also confirms that vibration can improve material removal rates by about 50.5% and improve the surface quality by about 25.4%.